Social media and memes. How have memes contributed to the creation of a new age digital culture? - Antoniou, Athena Diana (Τμήμα Πολυμέσων Και Γραφικών Τεχνών, Σχολή καλών και εφαρμοσμένων τεχνών, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2019)
Our modern world can be summarized in one phrase: social media. This evolutionary wave of connectivity, sharing and communication has been the dawn of a digital new world order, in which many communities have formed in order to bond and connect over shared interests. The “internet meme” is a phenomenon so interesting that it deserves a full, in-depth analysis, which is what will follow in this dissertation. Extensive research was carried out for the furtherment of this study, from several articles, books, videos and websites. There hasn’t been enough academic writing on this topic even though it’s such an interesting phenomenon. In order to get an inside-view of what the meme community is like and what it’s like to be a part of it, information was gathered from 24 individuals who were meme enthusiasts and in-touch with the meme community. The purpose of the questionnaire was to extract qualitative data and delve deeper into the world of internet memes. The information that surfaced indicated to a strong feeling amongst meme followers of a belonging in a community. The participants also helped with making certain aspects of memes clearer, such as why something becomes a meme, how does a meme evolve and what is its purpose. The answers were very insightful, and made it seem as though memes are not just funny pictures as most people presume; they are in fact a very important part of the every day lives of many individuals who benefit from the comedic ideas by coping with tough situations. In order to gather even more information about the emotional and psychological effects memes have on individual, focus groups and one-on-one interviews are advised.
Keywords: social media; internet meme; new age digital culture; The evolution of memes